Pengaruh Motivasi Belajar, Fasilitas Belajar Dan Kepercayaan Diri Terhadap Prestasi Mahasiswa Prodi Akuntansi Di Kota Batam - Sitompul, Megawati; Banjarnahor, Haposan (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to analyze the effect of learning motivation, learning facilities and self-confidence on student achievement in accounting study program in Batam City. This study used a descriptive and quantitative statistical approach with a population of Batam city students majoring in Accounting and the sample in this study totaling 100 respondents who were selected using a non-probability sampling technique and using a questionnaire as a data collection instrument. From the analysis of the data, it was found that learning motivation had an effect on learning achievement with t count (2.165) > t table (1.290), learning facilities had an effect on learning achievement with t count (1.001) > t table (1.290) and confidence had an effect on learning achievement with t count (4.478) > t table (1.290). Simultaneously the results of the F test of learning motivation, learning facilities and self-confidence affect learning achievement with an F count (49.188) > F table 2.70).